2011
DOI: 10.18202/jamal.2011.12.7139
|View full text |Cite
|
Sign up to set email alerts
|

14. Wujud, Makna dan Akuntabilitas “Amal Usaha” Sebagai Aset Ekonomi Organisasi Religius Feminis

Abstract: Abstrak: Wujud, Makna dan Akuntabilitas "amal usaha" Sebagai Aset Ekonomi Organisasi Religius Feminis. Riset ini mengeksplorasi wujud, makna dan akuntabilitas dari "amal usaha" sebagai aset ekonomi di "Persyarikatan Aisyiyah" sebagai suatu organisasi religius. Dengan menggunakan pendekatan fenomenologi, hasil riset ini menunjukkan bahwa Aisyiyah melakukan usaha mendapatkan laba untuk kepentingan organisasi. Temuan lebih lanjut menunjukkan bahwa, pertama, "amal usaha" merupakan media beribadah kepada Tuhan, dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…In the financial reports of business entities and conventional accounting, they must recognize these as part of them because they will only present information about the material. However, there needs to be more information, such as mental assets, spiritual assets, and other non-material information that influences the company's growth and development (Triyuwono, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In the financial reports of business entities and conventional accounting, they must recognize these as part of them because they will only present information about the material. However, there needs to be more information, such as mental assets, spiritual assets, and other non-material information that influences the company's growth and development (Triyuwono, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Djamhuri (2011) revealed that accountability cannot be generalized in various contexts. Accountability is also likely influenced and shaped by the environment and religion (Randa, 2011;Widati et al, 2011). Therefore, this research aims to reveal the accountability that Tadulako University has carried out during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Saad et al (2014) found that accountability in the Zakat institution is driven by the Islamic foundation, which cannot be separated from the Islamic teachings and pathways. Widati et al (2011) also examined the Aisyiyah Organization using a phenomenological approach and uncovered that the accountability of the committees involved two things: bringing material benefits and realizing the organization's vision and mission. Siskawati and Surya (2015) inspected the accountability of mosques in West Sumatra using a case study approach.…”
Section: Introductionmentioning
confidence: 99%